INTEGRATING ETHNOCHEMISTRY AND AUGMENTED REALITY TO SUPPORT CHEMICAL REPRESENTATION AND PROBLEM-SOLVING SKILLS IN ACID BASE CHEMISTRY - Sunniarti Ariani; Dyah Puspitasari Ningthias; Weny Amanatul Hidayah; Yunita Ardiyanti (Jurnal Ilmu Pendidikan Indonesia, 2026)
Problem-solving and representational competence are critical yet challenging skills for students to master in chemistry education, particularly in abstract topics like acid-base chemistry. This study investigates the effectiveness of an innovative learning module that integrates local cultural knowledge (ethnochemistry) with immersive digital visualization technology (Augmented Reality/AR) to address these challenges. Utilizing a quantitative pre-experimental design with a one-group pretest posttest model, the study was conducted with 26 second-semester undergraduate chemistry education students at Universitas Mataram, Indonesia. Data were collected using validated chemical representation competence and problem-solving skills tests, alongside observation sheets. The results of a paired-sample t-test revealed statistically significant improvements in both domains (p < 0.001). The students' mean score for chemical representation competence increased from 40.77 to 66.92 (N-gain = 0.45, medium improvement), with a large effect size (Cohen’s d = 1.58). Concurrently, problem-solving skills demonstrated a high advancement, shifting from a mean score of 39.23 to 84.23 (N-gain = 0.74, high improvement; Cohen’s d = 1.53). Qualitative observation data supported these findings, showing high student engagement and active conceptual reasoning during the intervention. The findings suggest that the module's strength lies in its complementary synergy: ethnochemistry provides a familiar macroscopic anchor that contextualizes learning, while AR functions as a representational scaffold that reduces cognitive load by visualizing invisible submicroscopic molecular interactions. This study provides practical implications for designing culturally responsive and technology-enhanced instructional materials in higher education.